PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MODEL PROYEK UNTUK MELATIHKAN BERPIKIR KREATIF SISWA SMP MATERI GERAK BENDA - Karlin, Karlin; Widodo, Wahono; Madlazim, Madlazim (Universitas Negeri Surabaya, 2016)
This research aims to develop valid, practical, and effective science learning material using project learning model to facilitate creative thinking skills on object motion in junior high school. Design of the development are used follow 4D model desin. The learning kit being validated by experts are syllabus, lesson plan, student work sheet, handout, and creative thinking question. The objective of this research was to trial learning materials in 39 grade VIII students in SMPN 31 Surabaya with One Group Pretest Postes Design. The results were analyzed by descriptive quantitative and qualitative. The result were obtained shows that the developed learning materials are: (1) Validity of learning material valid category (3,58); (2) Practicality based on: a) Feasibility of instruction good category (3,9); b) Readability of worksheets and student’s book students stating that the content and appearance of worksheets and student’s book good category; (3) Effectiveness based on: a) Student’s activities high category (93%); b) Result of creative thinking students increased with medium category (N-Gain: 0,62), result of creative thinking students increased with medium category (N-Gain:0,674) in fluency thinking aspect, result of creative thinking students increased with high category (N-Gain:0,726) in flexible thinking aspect, result of creative thinking students increased with medium category (N-Gain:0,531) in original thinking aspect, and result of creative thinking students increased with medium category (N-Gain:0,530) in elaboration thinking aspect; c)The response of students very positively (92%). The conclusion of this research that science learning material developed base on project learning model valid, practical, and effective to facilitate student’s creative thinking in junior high school. Penelitian ini bertujuan mengembangkan perangkat pembelajaranIPA model proyek yang valid, praktis, dan efektif untuk melatihkan berpikir kreatif siswa SMP materi gerak benda. Rancangan pengembangan yang digunakan mengikuti rancanagn model 4D. Perangkat pembelajaran yang dikembangkan meliputi Silabus, RPP, Handout siswa, LKP, dan Soal berpikir kreatif. Sasaran penelitian adalah perangkat pembelajaran yang diujicobakan pada 39 siswa kelas VIII SMPN 31 Surabaya dengan rancangan menggunakan One Group Pretest-Postest Design. Hasil penelitian dianalisis secara deskriptif kuantitatif dan kualitatif. Hasil yang diperoleh menunjukkan bahwa perangkat pembelajaran yang dikembangkan dinyatakan: (1) Validitas perangkat kategori valid (3,58); (2) Kepraktisan perangkat yang meliputi: a) Keterlaksanaan baik (3,9); b)Keterbacaan Handout dan LKP baik; (3) Keefektifan perangkat pembelajaran yang meliputi: a) Aktivitas siswa dengan kategori tinggi (93%); b) Hasil berpikir kreatif siswa mengalami peningkatan dengan kategori sedang (N-Gain: 0,62), pada aspek berpikir lancar (fluent) mengalami peningkatan berkategori sedang (N-Gain: 0,674), berpikir luwes (flexible) mengalami peningkatan berkategori tinggi (N-Gain: 0.726), berpikir orisinal (original) mengalami peningkatan berkategori sedang (N-Gain: 0,531), dan berpikir terperinci (elaboration) mengalami peningkatan berkategori sedang (N-Gain: 0,530); c) Respon siswa terhadap perangkat dan model pembelajaran sangat positif (92%). Simpulan penelitian ini bahwa perangkat pembelajaran IPA model proyek valid, praktis, dan efektif untuk melatihkan berpikir kreatif siswa SMP.